The Effects of Increased Screen Time on Cognitive Development in Children - Yadav, Amit Kumar (Journal of Research in Vocational Education, 2025)
The passing of the Online Safety Act into law in October 2023 by the parliament of the United Kingdom has brought back the studies on the impact of technology on the cognitive development of children, centre stage. With multiple studies showing an average screen time of over 4 - 7 hours daily among children in the age group of 8 - 18 globally, it is crucial that its long - term impact be factored in carefully before it begins to impact an entire generation adversely.